3D Wide FOV Scanning Measurement System Based on Multiline Structured-Light Sensors. (27th March 2014) - Gao, He; Zhou, Fuqiang; Peng, Bin; Wang, Yexin; Tan, Haishu
Abstract : Structured-light three-dimensional (3D) vision measurement is currently one of the most common approaches to obtain 3D surface data. However, the existing structured-light scanning measurement systems are primarily constructed on the basis of single sensor, which inevitably generates three obvious problems: limited measurement range, blind measurement area, and low scanning efficiency. To solve these problems, we developed a novel 3D wide FOV scanning measurement system which adopted two multiline structured-light sensors. Each sensor is composed of a digital CCD camera and three line-structured-light projectors. During the measurement process, the measured object is scanned by the two sensors from two different angles at a certain speed. Consequently, the measurement range is expanded and the blind measurement area is reduced. More importantly, since six light stripes are simultaneously projected on the object surface, the scanning efficiency is greatly improved. The Multiline Structured-light Sensors Scanning Measurement System (MSSS) is calibrated on site by a 2D pattern. The experimental results show that the RMS errors of the system for calibration and measurement are less than 0.092 mm and 0.168 mm, respectively, which proves that the MSSS is applicable for obtaining 3D object surface with high efficiency and accuracy.